Depression is linked to uncontrolled hypertension: a case–control study from Karachi, Pakistan. (December 2014) - Almas, Aysha; Patel, Junaid; Ghori, Uzma; Ali, Ambreen; Edhi, Ahmed Iqbal; Khan, Mohammad Ataullah
Abstract Background: High blood pressure is an important risk factor for cardiovascular disease and may be more prevalent in persons with psychopathology. Objective: To determine the association between uncontrolled hypertension with depressive and anxiety disorders in two tertiary care centers in Karachi. Methods: It was a case–control study conducted in two hospitals in Karachi. Cases were patients with uncontrolled hypertension and controls were patients with controlled hypertension. History of anxiety or depression as measured by Hospital Anxiety and Depression Scale (HADS) was the exposure. HADS of >8 was suggestive of having anxiety or depression. Results: A total of 700 participants were approached, out of whom 590 fulfilled the inclusion criteria and consented to participate, 323 (54.7%) participants were enrolled as cases and 267 (45.3%) as controls. Mean (SD) age was 54.98 (12.38) years, 229 (38%) were males. Odds ratio (OR) (95% CI) of having uncontrolled hypertension and being depressed (HADS-D > 8) was 2.02 (1.44–2.83), p value ≤ 0.001. The association remained significant even after adjusting for age and gender in Model 1 OR (95% CI): 1.82 (1.27–2.60), p value = 0.001, ethinicity and education in Model 2 OR (95% CI): 1.87 (1.29–2.71), p value = 0.001 and comorbids, history of hospitalization body mass index in Model 3 OR (95% CI): 1.94 (1.31–2.85), p value = 0.001. Conclusion: There is association between uncontrolled hypertension and depression that is independent of sociodemographic factors, comorbids and history of hospitalization.